Recursos alimentares e forrageamento de duas espécies de abelhas sem ferrão - Melipona (Melikerria) fasciculata Smith, 1854 e Melipona flavolineata Friese, 1900 (Apidae, Meliponini) - na região da Baixada Maranhense, Brasil - GOSTINSKI, Luana Fontoura (2018)
The bees are one of the most important pollinators of native plants and crops, in a way that the plants are benefited with the gene flow and the bees acquire food and substrate for nesting. In this thesis, two model species were selected for study: Melipona fasciculata and M. flavolineata, widely used on stingless beekeeping in one of the major poles of honey harvest in Maranhão, at the Baixada Maranhense. Thus, this thesis aimed to identify the main floral resources used by both species, as well as evaluate the correlation of the weather factors, the temperature, intranidal humidity and daily flying activity. Both species were observed on a meliponary at the municipality of Bequimão, Maranhão, Brazil, for one year, with monthly observation from September/2014 to July/2015. Pollen loads were collected from the bees returning to the colony, to evaluate the plant species used by them. Besides that, the daily flying activity and the resource colect were also registered. The temperature and relative humidity from inside the colonies and from the local environment were sampled during the same period, everyone hour. The external and internal temperature of the colonies of the two species were strongly correlated, as well as the inside and outside relative humidity. The bee flying activity corresponded positively with the local temperature, beggining at 6:00 am when the temperature was around 25 ºC, after which there were peaks of activity from 10:00 am - 02:00 pm in M. fasciculata, from 11:00 am - 02:00 pm in M. flavolineata. For both species there was a higher tendency of pollen harvested during the highest average of relative humidity and lowest temperature. In relation to the nectar harvest, the higher tendecy was on the lowest averages of external humidity and highest temperature. The most frequent plant families in the pollen spectrum of the two species of Melipona were Arecaceae (22%), Fabaceae (18.5%), Myrtaceae (9.6%), Melastomataceae (8.4%) and Lecythidaceae (6%).